Efficacy of a high-purity factor IX concentrate in hemophilia B patients undergoing surgery - Rasi,Vesa (2002)
A plasma derived, high purity, solvent-detergent treated and subsequently nanofiltered factor IX concentrate (BEMOFIL) was evaluated in 19 hemophilia B patients, including four with severe, thirteen with mild or moderate type of disease and two hemophilia B carriers undergoing 31 surgical procedures. The mean in vivo recovery was 52 %, range 36 - 76 %. The mean preoperative plasma factor IX activity after the initial loading dose was 0.86 IU mL-1, range 0.59 - 1.32 IU mL-1. In eight major orthopedic procedures, the mean usage of factor IX was 44600 IU or 574 IU kg-1 during the hospital stay, mean 11.6 days. Thromboprophylaxis was not used. The hemostatic efficacy was evaluated good in all cases and there were no thromboembolic complications. In conclusion, BEMOFIL used as bolus dosing was found to be safe and effective in achieving hemostasis in subjects with hereditary F IX deficiency undergoing surgery.